Ghana Rising : Accelerating Economic Transformation and Creating Jobs - World Bank (World Bank, Washington, DC, 2021)
Ghana has been a rising growth star and a beacon of hope in West Africa. Strong economic growth over the past two decades led to a near doubling of GDP per capita, lifting the country through the threshold for middle-income status in 2011. GDP per capita grew by an average of 3 percent per year over the past two decades, putting Ghana in the top ten fastest growing countries in Sub-Saharan Africa (SSA). A rising tide has tended to lift all boats. Poverty rates more than halved between 1998 and 2016, and the extreme poverty rate declined from 36.0 percent in 1991 to 8.2 percent in 2016. The net primary school enrollment rate rose from 62.5 percent in 2000 to 86.0 percent in 2019. This progress has motivated the government’s goal to lift the country to high-income status by 2057. The focus of this Country Economic Memorandum (CEM) is to review options for Ghana to create enough higher quality jobs through economic transformation. Economic transformation, or inclusive productivity growth, occurs as people and resources shift from lower to higher productivity activities. It raises household incomes and living standards, thereby lifting people out of poverty. It can be achieved through the movement of workers and other resources between firms and sectors, or through workers staying within existing firms that benefit from within-firm productivity growth by adopting better technologies and capabilities.